Hidden Curriculum Analysis: Cultural Content of EFL Textbook - Fikri, Abdul; Kardena, Absharini (International Journal of English Education and Linguistics (IJoEEL), 2024)
Curriculum is a fundamental framework in education. Some factors that influence the educational process sometimes cannot always be seen directly as known as hidden curriculum. The objective of this research is to analyse hidden curriculum specifically cultural content in EFL textbook. This research is a descriptive qualitative research. The data were collected from an EFL English textbook named “Bahasa Inggris Tingkat Lanjut”. The researchers analysed the data based on a theory of Cortazzi & Jin, (1999). The result of this research reveals 6 source cultural contents, 6 international cultural contents, and 3 target cultural contents. The total cultural contents in EFL textbook are 15 cultural contents. Most of these cultural contents are presented in the EFL textbook in form of folktales.